Regional Economic Outlook, October 2014 : Staying the Course. (Regional Economic Outlook; Regional Economic Outlook, 2014)
Growth in much of Sub-Saharan Africa is expected to remain strong, driven by efforts to invest in infrastructure and strong agricultural production. The current Ebola outbreak in Guinea, Liberia, and Sierra Leone is exacting a heavy toll, with spillovers to neighboring countries. External threats to the region's overall positive outlook include global financial conditions and a slowdown in emerging market growth.